ANALYSIS OF OPPORTUNITIES AND CHALLENGES FOR DEVELOPMENT OF THE MALINAU REGENCY (INDONESIA) - MALAYSIA BORDER AREA - Bilung Ajang; Kresna Adhi Prahmana; Widyawati (International Journal of Multidisciplinary Reseach, 2026)
Malinau Regency shares a border with Malaysia, but progress has been uneven. The Human Development Index rose to 74.72 in 2024, while the poverty rate also rose to 6.94 percent. Residents in remote sub-districts remain isolated and dependent on supplies from Malaysia. This study aims to map the opportunities and challenges for development in Malinau's border areas while developing strategies that balance security and well-being. The method used is a qualitative case study design. The population comprised communities and stakeholders in five border sub-districts: Kayan Hulu, Kayan Selatan, Bahau Hulu, Pujungan, and Sungai Boh. The sample was selected purposively, consisting of twelve key informants, ranging from regional planners, border managers, sub-district heads, and traditional leaders to traders, health workers, and teachers. Data were collected through in-depth interviews, observations, and document reviews, then analyzed using the Miles, Huberman, and Saldaña model. Data were summarized, presented, and conclusions were drawn, supported by a SWOT analysis using the IFAS and EFAS matrices. As a result, the biggest challenges are isolation, high costs in the region, cross-border dependencies, and fragmented coordination. Opportunities lie in resource wealth, indigenous social capital, and support for national priorities. An IFAS score of 2.37 and an EFAS score of 2.66 place Malinau in Quadrant I with coordinates of +0.75 and +0.70, respectively, suggesting an aggressive strategy. However, these opportunities can only be achieved if internal weaknesses are addressed first. In conclusion, Malinau's underdevelopment is structural. Opportunities will only be unlocked if connectivity, basic services, the local economy, and integrated data are improved within a welfare border framework.